ANALYSIS OF JAVANESE LANGUAGE VOCABULARY SKILL FOR ELEMENTARY SCHOOL STUDENTS IN KEBUMEN DISTRICT - Liftahul Sekar Aji; Sugiharti Sugiharti; Moh Salimi (Universitas Sebelas Maret, 2018)
Students are more proficient in foreign languages and Indonesian, this can be seen from everyday conversations that rarely use Javanese. This study aims to determine the vocabulary mastery of Javanese language in elementary school students. This research method uses qualitative descriptive research method. The subjects of this study were the fifth grade students of Kutosari 7 State Elementary School and Pekunden Elementary School. Data collection was carried out using questionnaire instruments and tests in the form of student worksheets. The results of this study indicate that elementary school students lack mastery of Javanese language.